Initial experience with breast conserving surgery in Jos - Ale, Alexander F.; Isichei, Mercy W.; Ismaila, Bashiru O.; Misauno, Michael A. (International Journal of Research in Medical Sciences, 2023)
Background: Breast conserving surgery is the treatment of choice in the surgical management of early-stage breast cancer in developed countries, while mastectomy has remained the most practiced surgical treatment in developing countries. The aim of the study was to describe the outcomes of a cohort of patients who had breast conserving surgery in a developing country. Methods: The study is a retrospective review of patients who were offered breast conserving surgery between January 2018 and December 2020 at the Jos University Teaching Hospital and FOMAS Hospital. Results: A total of 110 female patients had surgery for breast cancer in the study period. Of this number, eleven (10%) patients whose ages ranged from 28-70 years with a mean age of 53.5 years (SD=12.9 years) had breast conserving surgery, while 99 (90%) had mastectomy. A painless lump on self-breast examination was the most common reason for presentation in those who had breast conserving surgery. Most of the patients who had breast conserving surgery presented with tumor stage T2N1M0. Quadrantectomy was done in 7 (63.6%) patients while 4 (36.4%) had wide local excision. No patient developed any postoperative complication. No patient required re-excision due to positive margins. Three (27.3%) patients had only adjuvant hormonal therapy. Eight (72.7%) patients had radiotherapy following surgery, while 3 (27.3%) patients had only breast conserving surgery for loco-regional control. All patients had a minimum follow up of 2 years with no recurrence or mortality. Conclusions: Breast conserving surgery can be safely practiced as an alternative to mastectomy in carefully selected patients with early breast cancer with good outcomes.